From green technology development to green innovation: inducing regulatory adoption of pathogen detection technology for sustainable forestry - Hall, Jeremy; Matos, Stelvia; Bachor, Vernon (Springer, 2017)
Technological entrepreneurship has been widely acknowledged as a key driver of modern industrial economies, and more recently, a panacea for environmental and social problems. However, our current understanding of how green-technology ventures emerge and diffuse more sustainable innovations remains limited. We advance theory on green entrepreneurship by drawing on institutional work to refine and extend our understanding of how entrepreneurs may influence government policies and practices in their attempts to diffuse green technology. We develop a theoretical framework that combines institutional work with a search tool, the technological, commercial, organizational, and societal (TCOS) framework of innovative uncertainties, which identifies key opportunities, hurdles, and potential unintended consequences at early stages of technology development. We present a detailed case study of a potential university-based green-tech venture developing pathogen detection technology for forestry protection. Foreign pathogens spread by international trade can have major detrimental impacts on forests and the industries that rely on them. Our analysis found that green technology demonstrating technological feasibility is necessary but not sufficient; green-tech ventures must also engage in institutional work, in this case, articulating the technology’s benefits to regulators to establish legitimacy and avoid misuse that can hinder its adoption. We thus add to previous studies by emphasizing that institutional work could be a main activity for a green-tech venture, a core entrepreneurial strategy rather than an afterthought.